A survey experiment on post-Dobbs abortion bans - Laurel Elder; Steven Greene; Mary-Kate Lizotte (Research & Politics, 2025)
In the wake of the Supreme Court’s Dobbs v. Jackson decision overturning Roe v. Wade, the American abortion policy landscape has been significantly altered. Through a novel survey experiment, we examine public opinion on 6-week versus 12-week abortion bans in this new context, testing whether 12-week bans are perceived as a more moderate position and garner greater support. Surprisingly, we find that Americans do not meaningfully distinguish between 6-week and 12-week bans. This suggests that attempts by some Republican officials to navigate the post-Dobbs landscape by proposing “moderate” abortion restrictions may be ineffective. However, we find that framing does matter: pro-life framing of bans increases support for candidates who endorse them, while pro-choice framing increases support for candidates who oppose them. Overall, our findings indicate that in the post-Dobbs era, the abortion debate has largely been flattened to a binary of “ban” versus “no ban,” rather than distinctions between ban timelines. As the post-Dobbs legal and political environment continues to evolve, our research provides valuable insights into how the public is responding to this new landscape of abortion politics in America.